Nature Streaming: Contrasting the Effectiveness of Perceived Live and Recorded Videos of Nature for Restoration. Issue 9 (November 2019) - Snell, Tristan Leslie; McLean, Louise Anne; McAsey, Finn; Zhang, Michael; Maggs, Diana
This study investigated whether a video of a natural landscape would be more effective for restoration, including attention restoration and recovery from stress, when perceived as live rather than recorded. In total, 60 participants undertook attention-expending and stress inducing tasks, before being randomly assigned to one of three conditions (perceived live video, recorded video, and control). Attention recovery was assessed using Digit Span Backwards (DSB) and the Necker Cube Pattern Control (NCPC) pre- and post-condition, while stress was measured via skin conductivity, heart rate, and heart rate variability. We found that only participants in the live group significantly improved on the NCPC, whereas stress recovery was similar for both perceived live and recorded groups. Our findings suggest that a perceived live stream of nature may allow for greater cognitive inhibition, an important aspect of learning, whereas both perceived live and recorded videos effectively reduced sympathetic stress responses.